The Role of Life Stressful Events, Emotional Distress Tolerance, and Perceived Gender Discrimination in Predicting Suicidal Thoughts Among Women with Experiences of Domestic Violence - Gholami, Amin Allah; Davoodvandi , Zahra; Abbasgholipoor , Souraya; Karami, Zahra; Gholami, Forud (KMAN Counseling & Psychology Nexus, 2024)
The objective of this study was to investigate the predictive roles of life stressful events, distress tolerance, and perceived gender discrimination in suicidal ideation among women with experiences of domestic violence in Tehran. This research employed a correlational descriptive design with a sample of 400 women selected based on Krejcie and Morgan’s table through convenience sampling from social service centers and shelters in Tehran. Data were collected using standardized instruments: the Beck Scale for Suicidal Ideation, Holmes and Rahe Stress Scale, Distress Tolerance Scale, and the Perceived Gender Discrimination Scale. Pearson correlation coefficients were computed to examine the bivariate relationships, and multiple linear regression analysis was used to identify the predictive power of the independent variables on suicidal ideation. Data analysis was conducted using SPSS version 27. Pearson correlation results indicated that suicidal ideation had a significant positive correlation with life stressful events (r = 0.62, p < .001) and perceived gender discrimination (r = 0.49, p < .001), and a significant negative correlation with distress tolerance (r = -0.55, p < .001). The multiple regression model including life stressful events and distress tolerance was significant, F(2, 397) = 134.85, p < .001, explaining 46% of the variance in suicidal ideation (R² = 0.46). Life stressful events (β = 0.48, p < .001) and distress tolerance (β = -0.39, p < .001) were both significant predictors. The findings highlight the significant role of life stress and emotional resilience in predicting suicidal ideation among women experiencing domestic violence. These results underscore the importance of targeted interventions focusing on stress reduction and distress tolerance to mitigate suicide risk in this vulnerable population.